2017
DOI: 10.3390/ijerph14101140
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, Ecological and Human Health Risks, and Seasonal Variations of Phenolic Compounds in Surface Water and Sediment of a Potential Polluted River Basin in China

Abstract: Five phenolic compounds in water and sediment of Yinma River Basin were investigated. The average concentration of phenol was the highest in water samples as well as in sediment samples during the wet season, 101.68 ng/L and 127.76 ng/g, respectively. 2,4,6-Trichlorophenol (2,4,6-TCP) and pentachlorophenol (PCP) was not detected in some sampling sites. Shitou Koumen Reservoir and the neighboring area were the severest areas of phenolic pollution. The lower reach was more polluted in three water seasons than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…[41,46] The concentrations of PCs obtained in African countries are lower than a study done in Hungary (nd to 2910 μg kg −1 ) by Faludi et al and in China at Weihe River (3.54 × 10 3 to 34.09 × 10 3 μg kg −1 ) by Chen et al, but higher than those reported in China (0.0963-0.448 μg kg −1 ) at Yinma River Basin by Zhou and Sun. [44] In sludge samples, the concentrations obtained in this work (0.86-310 μg kg −1 ) were lower than those reported in Japan (0.003-3600 μg kg −1 ), but higher than those reported in Taiwan (2.72-6.35 μg kg −1 ). [25,47] The difference in concentrations in the various matrices from different countries could be due to the increase in industrialization, which continues to cause pollution which has a direct negative impact on the ecosystem.…”
Section: F I G U R Econtrasting
confidence: 72%
See 1 more Smart Citation
“…[41,46] The concentrations of PCs obtained in African countries are lower than a study done in Hungary (nd to 2910 μg kg −1 ) by Faludi et al and in China at Weihe River (3.54 × 10 3 to 34.09 × 10 3 μg kg −1 ) by Chen et al, but higher than those reported in China (0.0963-0.448 μg kg −1 ) at Yinma River Basin by Zhou and Sun. [44] In sludge samples, the concentrations obtained in this work (0.86-310 μg kg −1 ) were lower than those reported in Japan (0.003-3600 μg kg −1 ), but higher than those reported in Taiwan (2.72-6.35 μg kg −1 ). [25,47] The difference in concentrations in the various matrices from different countries could be due to the increase in industrialization, which continues to cause pollution which has a direct negative impact on the ecosystem.…”
Section: F I G U R Econtrasting
confidence: 72%
“…[14,41] The concentration obtained in African countries (nd to 98 μg L −1 ) were higher than countries overseas with concentrations ranging from 0.0065 to 0.0308 μg L −1 in Hungary, Danube River, [42] 0.06 to 14.1 μg L −1 in Northwest China, Weihe River, [43] and 0.053 to 0.339 μg L −1 in China, Yinma River Basin. [44] However, a study done by Faludi et al in Hungary (Lake Balaton) revealed higher concentrations of 20.6-888.0 μg L −1 compared to African countries. [45] In wastewater, the concentrations observed in this study (4.12-83.30 μg L −1 ) were higher compared with other South African provinces like Eastern Cape (nd to 2.20 μg L −1 ) as reported by Farounbi and Ngqwala.…”
Section: F I G U R Ementioning
confidence: 92%
“…PNEC is the limit concentration or the predicted no effect concentration [18]. In this study, the Vietnamese have used a standard limit of 0.3 mg.kg −1 for vegetables [19].…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, they are also a kind of important organic raw materials in the field of agricultural production and are widely used in the manufacture of pesticides, insecticides, and herbicides [ 197 , 198 , 199 ]. Their wide use in industry and agriculture makes them a large number of residues in the environment and a common organic pollutant in water, which have potential carcinogenicity, teratogenicity, and mutagenicity, with wide source, great harm and refractory degradation [ 200 , 201 , 202 ]. Among them, phenol and its derivatives (such as bisphenol A, chlorophenol, nitrophenol, etc.)…”
Section: Applications Of Photocatalytic Technology In Water Treatmentmentioning
confidence: 99%